2004
DOI: 10.1126/science.1103440
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Glycosphingolipid Recognition by NKT Cells

Abstract: NKT cells represent a distinct lineage of T cells that coexpress a conserved alphabeta T cell receptor (TCR) and natural killer (NK) receptors. Although the TCR of NKT cells is characteristically autoreactive to CD1d, a lipid-presenting molecule, endogenous ligands for these cells have not been identified. We show that a lysosomal glycosphingolipid of previously unknown function, isoglobotrihexosylceramide (iGb3), is recognized both by mouse and human NKT cells. Impaired generation of lysosomal iGb3 in mice la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
887
2
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 885 publications
(927 citation statements)
references
References 31 publications
19
887
2
11
Order By: Relevance
“…[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34]. iNKT cells are abundant in the liver and rapidly secrete large amounts of immunoregulatory cytokines such as IFN-g and IL-4 after stimulation through their TCR [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…[31] and phosphoethanolamine [32] have recently been identified as ligands for iNKT cells, although all of these activate iNKT cells to a lesser degree than a-GalCer. Although lysosomal glycosphingolipid, isoglobotrihexosylceramide has been reported as a possible endogenous ligand for iNKT cells [28,33], a recent study argues against this possibility [34]. iNKT cells are abundant in the liver and rapidly secrete large amounts of immunoregulatory cytokines such as IFN-g and IL-4 after stimulation through their TCR [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…GM1/GA1 can no longer be degraded to GM2/GA2 and GM3/GA3 and represent the most prominent glycolipids accumulating in patients and mice deficient in bGal [44][45][46]. However, the lack of gangliosides such as GM2/GA2 or GM3/GA3 probably does not explain deficient development of Va14i NKT cells in bGal -/-mice since mice lacking ganglio-series glycolipids as a result of genetic deficiency of GM2 or GM3 synthase, i.e., the key enzymes for their synthesis, displayed no apparent defect in development of Va14i NKT cells [28]. Lactosylceramide does not accumulate in bGal -/-mice because its degradation, involving the removal of terminal b-galactose residues, can be exerted by an alternative enzyme, galactosylceramidase (EC 3.2.1.46) [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mouse models of lipid storage diseases have been studied with respect to the relevance of lysosomal enzymes and lipid transfer proteins for stimulation and selection of a specialized population of T cells, i.e., Va14i NKT cells, recognizing glycolipid antigens in the context of CD1d antigen-presenting molecules. These studies revealed that Hexb- [28,32], Hexa- [32], aGal- [32], bGal- [32], saposin- [29], or NPC1- [31,32] deficient mice have reduced numbers of Va14i NKT cells and, in the cases of Hexb -/-, bGal -/-, saposin -/-, and NPC1 -/-mice, defects in lipid antigen presentation. Va14i NKT cell deficiency has originally been explained as a result of lacking iGb3 in the case of Hexb -/-, and of impaired saposin-mediated lipid transfer onto CD1d molecules in the case of saposin -/-mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the lysosomal glycosphingolipid (GSL) isoglobotrihexosylceramide (iGb3) was described as an endogenous, and perhaps the selecting, ligand for iNKT cells [66], it faced a good deal of skepticism, mainly because humans are believed to lack functional α1,3 Galactosyltransferase [67,68], an enzyme thought to be critical to the synthesis of iGb3. Two papers published last year raised some doubts regarding the role of iGb3 as a self-antigen.…”
Section: Endogenous Inkt Cell Antigensmentioning
confidence: 99%